Pengaruh Pendidikan Kesehatan Menggunakan Media PuzzleTerhadap PengetahuanTentang Karies Pada Siswa SDN 002 Samarinda - Febry Nurhani Putri, Winanda (STIKes Medistra Indonesia, 2024)
Dental caries is one of the oral health problems that often occurs in children. The prevalence of dental caries in children in Kalimantan Tumr was higher than the national prevalence. Efforts can be made to prevent dental caries in children are to improve children's behavioral domains related to the prevention of dental caries. This study aimed to analyze the effect of health education with puzzle media on knowledge and attitudes about dental caries in students of SDN 002 Loa Janan Ilir. The type of research was a pre-experimental study with a one group pretest-posttest design. Research intervention through health education with puzzle media. The research sample was 29 fourth grade students of SDN 002 Loa Janan Ilir who were determined by total sampling. Data collection was filled out questionnaires. Data analysis used Wilcoxon test. Univariate analysis showed that the number of students who had good knowledge and positive attitudes about preventing dental caries increased at posttest. Bivariate analysis showed that there were statistical differences in the knowledge (p-value = 0.000) and attitudes (p-value = 0.002) of respondents after being given the research intervention. There was an effect of health education using puzzle media on knowledge and attitudes about preventing dental caries in research respondents. It is hoped that the development and use of puzzles as a medium for health education in the implementation of health programs related to the prevention of dental caries in children.